Monoclonal antibodies to Staphylococcus aureus laminin-binding proteins cross-react with mammalian cells. - Mota, G F (1988)
We and others have previously shown that some microorganisms, including bacteria, express on their surfaces receptors that specifically recognize extracellular matrix proteins, such as laminin, fibronectin, or both. The ability of microorganisms to adhere and to invade might depend on the existence of receptors which could, thus, be correlated with pathogenicity. In the present paper, we report the isolation of five stable cell lines that were producers of monoclonal antibodies to Staphylococcus aureus laminin receptors. One of these antibodies, which was of the immunoglobulin M isotype, blocked the binding of laminin to bacteria before and after fixation and recognized the putative 52-kilodalton laminin-binding protein in whole bacterial extracts. Also, purified receptor was isolated by immunoaffinity chromatography and shown to bind laminin. Furthermore, the same antibodies bound the 67-kilodalton putative receptor from mouse melanoma cells and gave positive immunofluorescence reactions against mammalian tumor cells. These data strongly suggest either the evolutionary conservation of at least some sequences in both procaryotic and eucaryotic laminin-binding proteins or convergent evolution and positive selection of epitopes cross-reacting with laminin. Some of these antibodies to the procaryotic protein could therefore become useful markers for the expression of laminin receptors by cancer cells.